Micro PV Solar Station to Support Home Residential Using Multi-Level Inverter for Stand – Alone Load (Eurasian Journal of Engineering and Technology, 2023)
This study presents a standalone photovoltaic (PV) system for residential loads using a multi-level inverter. The system optimizes power output through maximum power point tracking (MPPT) control, enhances power conversion efficiency, and considers different weather conditions for reliable operation. The MPPT control algorithm tracks the maximum power point of the PV array, adjusting the operating point to maximize energy harvested from the solar panels. The multi-level inverter converts DC power into AC suitable for residential loads, reducing harmonic distortion and improving voltage quality. It also provides better control over power flow and seamless integration with residential loads. The system considers different weather conditions, such as variations in solar irradiance and temperature, to ensure optimal operation and robustness. The system is verified using MATLAB Simulink simulation software.